Thyroid Malignancy in Clinically Benign Cystic Thyroid Nodule Presentation (JBN (Jurnal Bedah Nasional), 2025)
Aim: Cystic thyroid nodule (CTN) is almost always considered benign (noncancerous). Approximately 1% of people with cystic nodules will develop cancer, but less than 3% of those with partly cystic nodules who do not exhibit any suspicious symptoms will do so. In contemporary clinical practice, the most dependable diagnostic method for choosing patients for surgery is fine-needle aspiration biopsy (FNAC).  However, because to the high frequency of insufficient smears and false-negative findings, FNAC has significant limits in instances with CTN. Two patients with cystic thyroid nodules were presented in this case report; however, further anatomical pathology reports following total thyroidectomy surgery revealed that the nodules were malignant. Case Presentation: This case report describes two cases of thyroid nodule patients who presented to Prof. Dr. RD Kandou Hospital. These patients had cystic thyroid nodules and subsequently underwent thyroidectomy due to large masses. Pathological examination was conducted and confirmed thyroid malignancy in both cases, specifically follicular variant papillary thyroid carcinoma. Conclusion: Ultrasound and FNAC examinations have limitations in detecting thyroid malignancies especially for large cystic thyroid nodule. Large nodule sizes and the inability to sample the whole lesion may potentially contribute to false negative results in FNAC. The experience of the operator also will determine the occurrence of false negatives in the ultrasound. Therefore, as clinician we should be aware there were potency of malignancy even in cystic thyroid nodule cases.